Vertical Transmission of Trypanosoma Cruzi in a Non-Endemic Country: Histology of the Infected Placenta. (November 2021) - Keogh, Anna; Ferguson, Wendy; Nolder, Debbie; Doyle, Emma; McEntagart, Noel
Chagas disease, once confined to rural Latin America is an increasing public health concern in non-endemic countries due to population movements. Here we present an unexpected finding of a placenta infected with T. cruzi from a Brazilian woman residing in Ireland. Histology of the placenta showed a lymphocytic chorioamnionitis with multinucleated giant cells (MNGCs) as well as cord vasculitis and funisitis. Amastigotes of trypanosomiasis were found in both cord and membranes. The placenta parenchyma, however, had no villitis or amastigotes and maturation was appropriate for gestation. To date, there have been few reported cases of vertical transmission in non-endemic countries. We discuss the histological findings and review the literature on potential modes of transmission from mother to fetus.